Ієрархічні моделі семантичної сегментації зображень в інформаційних технологіях - Єнацький, О. О. (ХНУРЕ, 2025)
In recent years, the rapid growth of visual data in fields such as medicine, security, and autonomous systems has highlighted the need for more advanced image processing techniques. Semantic segmentation, a fundamental task in computer vision, plays a crucial role in extracting meaningful information from images by dividing them into regions based on their content. This process is particularly important for applications like autonomous driving, medical diagnostics, satellite image analysis, and intelligent video surveillance systems.
Keywords: сегментація зображення; модель семантичної сегментації